Peran Guru Dalam Perencanaan Pelaksanaan dan Evaluasi Pembelajaran PPKN Terhadap Pembentukan Karakter Kejujuran Siswa di SMPN 35 Medan - Dewi Romantika Tinambunan; Jekson Saragih; Kania Nova Ramadani; Talita Sembiring; Abdinur Batubara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study is entitled the role of teachers in planning the implementation and evaluation of PPKN learning towards the formation of students' honesty character at SMP Negeri 35 Medan. The method used in this research is descriptive qualitative. Namely a research method that describes a condition or situation and events systematically. Data collection in the form of interviews with PPKN teachers. This research results in an understanding of the role of teachers in planning the implementation and evaluation of PPKN learning on the character of student honesty